Screening β-Arrestin Recruitment for the Identification of Natural Ligands for Orphan G-Protein–Coupled Receptors - Southern, Craig; Cook, Jennifer M.; Neetoo-Isseljee, Zaynab; Taylor, Debra L.; Kettleborough, Catherine A.; Merritt, Andy; Bassoni, Daniel L.; Raab, William J.; Quinn, Elizabeth; Wehrman, Tom S.; Davenport, Anthony P.; Brown, Andrew J.; et al. (Journal of biomolecular screening, 2013)
A variety of G-protein-coupled receptor (GPCR) screening technologies have successfully partnered a number of GPCRs with their cognate ligands. GPCR-mediated β-arrestin recruitment is now recognized as a distinct intracellular signaling pathway, and ligand-receptor interactions may show a bias toward β-arrestin over classical GPCR signaling pathways. We hypothesized that the failure to identify native ligands for the remaining orphan GPCRs may be a consequence of biased β-arrestin signaling. To investigate this, we assembled 10 500 candidate ligands and screened 82 GPCRs using PathHunter β-arrestin recruitment technology. High-quality screening assays were validated by the inclusion of liganded receptors and the detection and confirmation of these established ligand-receptor pairings. We describe a candidate endogenous orphan GPCR ligand and a number of novel surrogate ligands. However, for the majority of orphan receptors studied, measurement of β-arrestin recruitment did not lead to the identification of cognate ligands from our screening sets. β-Arrestin recruitment represents a robust GPCR screening technology, and ligand-biased signaling is emerging as a therapeutically exploitable feature of GPCR biology. The identification of cognate ligands for the orphan GPCRs and the extent to which receptors may exist to preferentially signal through β-arrestin in response to their native ligand remain to be determined.